Mortality of the scleractinian coral Cladocora caespitosa during a warming event in the Levantine Sea (Cyprus) - Jiménez, Carlos; Hadjioannou, Louis; Petrou, Antonis; Nikolaidis, Andreas; Evriviadou, Marina; Lange, Manfred A. (My University, 2016)
A mortality event of Cladocora caespitosa corals and the extent of bleaching, necrosis and pigmented areas in the colonies were studied at the southeastern coast of Cyprus during a prolonged period of higher than average sea temperature anomalies (summer/autumn 2012). With the use of scuba diving and image analysis software, we monitored the extent of mortality of 29 colonies of C. caespitosa by measuring and comparing the area percentage of healthy tissue, affected tissue (bleached, necrotic) and older mortality events (encrusted skeleton). In September 2012, on average, 24 % of the colonies surface area was affected (bleaching and/or necrosis). In October 2012, C. caespitosa showed on average 26.3 % of the colony surface area affected, evidence of continuing deterioration. At the same time, 10 % (3 of 29) of the colonies showed an increase in the pigmentation of previously bleached polyps in small and marginal areas (6–8 %). Irrespective of the amount, the regaining of pigments recorded is considered an important find. Corals and marine organisms in general in the Levantine Sea are affected greatly by warming events, to the extent where a very small percentage of polyps/colonies show resilience under thermal stress. Natural bleaching of C. caespitosa, even though limited to a few colonies and very small portions of tissue/polyps, was documented for the first time in the Levantine Sea. We conclude that temperature anomalies are associated with the mortality event. Whether prolonged higher temperature is the direct cause, or whether it acts synergistically with other factors should be the subject of further investigations.
Keywords: Cladocora caespitosa; Climate change; Coral; Coral bleaching; Ecological impacts; Levantine Sea